Navigated Intraoperative 2-Dimensional Ultrasound in High-Grade Glioma Surgery: Impact on Extent of Resection and Patient Outcome. Issue 4 (21st August 2019) - Moiraghi, Alessandro; Prada, Francesco; Delaidelli, Alberto; Guatta, Ramona; May, Adrien; Bartoli, Andrea; Saini, Marco; Perin, Alessandro; Wälchli, Thomas; Momjian, Shahan; Bijlenga, Philippe; Schaller, Karl; et al.
Abstract: BACKGROUND: Maximizing extent of resection (EOR) and reducing residual tumor volume (RTV) while preserving neurological functions is the main goal in the surgical treatment of gliomas. Navigated intraoperative ultrasound (N-ioUS) combining the advantages of ultrasound and conventional neuronavigation (NN) allows for overcoming the limitations of the latter. OBJECTIVE: To evaluate the impact of real-time NN combining ioUS and preoperative magnetic resonance imaging (MRI) on maximizing EOR in glioma surgery compared to standard NN. METHODS: We retrospectively reviewed a series of 60 cases operated on for supratentorial gliomas: 31 operated under the guidance of N-ioUS and 29 resected with standard NN. Age, location of the tumor, pre- and postoperative Karnofsky Performance Status (KPS), EOR, RTV, and, if any, postoperative complications were evaluated. RESULTS: The rate of gross total resection (GTR) in NN group was 44.8% vs 61.2% in N-ioUS group. The rate of RTV > 1 cm 3 for glioblastomas was significantly lower for the N-ioUS group ( P < .01). In 13/31 (42%), RTV was detected at the end of surgery with N-ioUS. In 8 of 13 cases, (25.8% of the cohort) surgeons continued with the operation until complete resection. Specificity was greater in N-ioUS (42% vs 31%) and negative predictive value (73% vs 54%). At discharge, the difference between pre- and postoperative KPS was significantly higher for the N-ioUS ( P < .01). CONCLUSION: The use of an N-ioUS-based real-time has been beneficial for resection in noneloquent high-grade glioma in terms of both EOR and neurological outcome, compared to standard NN. N-ioUS has proven usefulness in detecting RTV > 1 cm 3 .